Combined modal parameters-based index for damage identification in a beamlike structure: theoretical development and verification - Fayyadh, M.M.; Razak, H.A.; Ismail, Z. (2011)
A new index for detecting the damage severity in structural elements by combining modal parameters is proposed in this study. The index is based on the combined effect of both the natural frequencies and mode shapes when a change in stiffness of the structural element occurs. In order to demonstrate the significance and capability of this new algorithm, the magnitude of damage was calculated from a finite element model of a beam-like structure model and comparisons with previous algorithms were carried out. The new index called Combined Parameter Index (CPI) compares the factor of reduction in stiffness according to reduction in natural frequencies and also the factor of reduction in stiffness according to change in mode shape. Various damage levels starting from reduction in stiffness of 1 were adopted to validate the sensitivity of the new index to detect the damage severity at various deterioration levels. Mid-span and quarter-span damage positions were adopted to verify the capability of the new damage index to detect the damage severity at various locations. Moreover, damage in support condition was investigated in order to ascertain that the new damage index can also identify support damage cases. The results indicate that the new index has better ability and higher sensitivity to determine the severity of the damage due to stiffness changes in the element or support. In addition, the CPI exhibits sensitivity to detect lower level of damage occurring at earlier stage by having the ability to detect a damage of 1 reduction in the structural element stiffness or elastic bearing stiffness.